1996
DOI: 10.1128/jb.178.20.6019-6024.1996
|View full text |Cite
|
Sign up to set email alerts
|

Purification and sequence analysis of 4-methyl-5-nitrocatechol oxygenase from Burkholderia sp. strain DNT

Abstract: 4-Methyl-5-nitrocatechol (MNC) is an intermediate in the degradation of 2,4-dinitrotoluene byBurkholderia sp. strain DNT. In the presence of NADPH and oxygen, MNC monooxygenase catalyzes the removal of the nitro group from MNC to form 2-hydroxy-5-methylquinone. The gene (dntB) encoding MNC monooxygenase has been previously cloned and characterized. In order to examine the properties of MNC monooxygenase and to compare it with other enzymes, we sequenced the gene encoding the MNC monooxygenase and purified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…The tryptophan 2-monoxygenase gene product itself produces indole acetamide, which can be converted to the auxin indole acetic acid by hydrolysis. Most flavin-containing proteins have a highly conserved motif located at the N terminus of the protein and involved in binding of the ADP moiety of FAD (35)(36)(37). The proposed motif (G-X-G-X-X-G-X-X-X-A) is preceded by three or four hydrophobic residues (38).…”
Section: Discussionmentioning
confidence: 99%
“…The tryptophan 2-monoxygenase gene product itself produces indole acetamide, which can be converted to the auxin indole acetic acid by hydrolysis. Most flavin-containing proteins have a highly conserved motif located at the N terminus of the protein and involved in binding of the ADP moiety of FAD (35)(36)(37). The proposed motif (G-X-G-X-X-G-X-X-X-A) is preceded by three or four hydrophobic residues (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that the highly specific 4M5NC monooxygenase from the 2,4-DNT pathway does not attack 3M4NC (9). The 3M4NC-2,3-dioxygenase from the 2,6-DNT pathway also appears to be highly specific for 3M4NC, with the only other substantial activity being against 3-methylcatechol.…”
Section: Revealed a Base Peak At M/z 158 And As Further Demonstratedmentioning
confidence: 99%
“…In Burkholderia sp. strain DNT (58,59,61,184,186,187) and Burkholderia cepacia R34 (85,86,131), the 4-methyl-5-nitrocatechol produced from 2,4-dinitrotoluene is oxidized by a monooxygenase to remove the second nitro group, forming 2,4,5-trihydroxytoluene, which is a substrate for meta ring cleavage (85). In contrast, metabolism of 2,6-dinitrotoluene by B. cepacia JS850 and Hydrogenophaga palleronii JS863 yields 3-methyl-4-nitrocatechol (Fig.…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%